Color Constancy Techniques (International Journal of Engineering and Computer Science, 2014)
Color constancy is the ability to estimate the color of light source. The color of light source may impact the appearance of object in the scene. Human has the natural tendency to recognize the actual color of object despite variations in the color of the light source. However, it is not easy for computer vision systems to discover the actual color of objects in the scenes. Several algorithms have been proposed to estimate the effect of color of light source on a digital image.  A review of the color constancy techniques is presented in the paper. Also, the comparative analysis of various color constancy techniques is discussed